The Impact of Investment Networks on Venture Capital Firm Performance: A Contingency Framework. (9th March 2016) - Bellavitis, Cristiano; Filatotchev, Igor; Souitaris, Vangelis
Abstract : Venture capital (VC) syndicates involve repeated transactions among partners and therefore possess network‐like characteristics. Although networks provide access to important externalities, extant literature has not studied the effects of the focal firm's resource needs on performance benefits arising from different network structures. We investigate the impact of two proxies for firm‐level resources, namely maturity and status, on the relationship between network cohesion and VC performance. We find that mature and high status VCs benefit less from network cohesion. We also show that maturity and status simultaneously determine the performance effects of network cohesion.